Effects of L-thyroxine treatment on early markers of atherosclerotic disease in children with subclinical hypothyroidism. Issue 1 (July 2016) - Cerbone, Manuela; Capalbo, Donatella; Wasniewska, Malgorzata; Alfano, Sara; Mattace Raso, Giuseppina; Oliviero, Ugo; Cittadini, Antonio; De Luca, Filippo; Salerno, Mariacarolina
Abstract : Objective: To investigate the effect of levothyroxine (L-T4) treatment on early markers of atherosclerotic disease in children with mild idiopathic subclinical hypothyroidism (SH). Design: Two-year, open, case–control prospective study. Methods: A total of 39 children, aged 9.18±3.56 years, with SH and 39 healthy controls were enrolled in the study. Waist-to-height ratio (WHtR), blood pressure, triglycerides, total cholesterol (total-C), HDL-C, LDL-C, non-HDL-C, triglycerides/HDL-C, atherogenic index (AI), homocysteine (Hcy), asymmetric dimethylarginine (ADMA), flow-mediated dilation (FMD) and intima–media thickness (IMT) were evaluated at baseline and after 2 years of L-T4 treatment in SH children and after 2 years of follow-up in controls. Results: At study entry WHtR was higher in SH subjects compared with controls (0.56±0.08 vs 0.49±0.07, P =0.04) and significantly decreased after 2 years of treatment (0.50±0.06, P <0.0001). Mean HDL-C levels (50.47±11.43 vs 61.06±13.83mg/dL, P =0.002) were lower, while triglycerides/HDL-C (1.63±1.07 vs 1.19±0.69, P =0.05), AI (3.32±0.90 vs 2.78±0.68, P =0.005), and Hcy (9.35±2.61 vs 7.71±1.94μmol/L, P =0.01) were higher in SH subjects compared with controls and improved after 2 years of treatment (HDL-C 56.26±13.76mg/dL, P <0.0001; triglycerides/HDL-C 1.23±0.78, P =0.006; AI 2.82±0.68, P <0.0001; and Hcy 8.25±2.09μmol/L, P =0.06). ADMA concentrations at baseline were higher in SH subjects compared with controls (0.77±0.21 vs 0.60±0.16μmol/L, P =0.001) and decreased after therapy (0.58±0.13μmol/L, P <0.0001). FMD, IMT and other metabolic parameters were not different among SH subjects and controls at baseline and after 2 years. Conclusions: Children with SH may have subtle pro-atherogenic abnormalities. Although L-T4 treatment exerts some beneficial effects, the long-term impact of therapy on metabolic outcomes in SH children still remains unclear.